Magnetic non-destructive evaluation of microstructural and mechanical characteristics of hardened AISI H13 die steel upon sustainable grinding - Awale A.S.; Srivastava A.; Kumar A.; Yusufzai M.Z.K.; Vashista M. (My University, 2025)
This paper describes the potential of non-destructive techniques such as micro-magnetic Barkhausen noise (MBN) to assess the grinding burn flaws in terms of microstructural and mechanical indices of hardened AISI H13 die steel. To overcome this grinding burn issue, minimum quantity lubrication grinding with eco-friendly machining fluids like paraffin oil (PO) and castor oil (CO) was adopted and compared its performance with well-established conventional grinding like wet and dry. Ground surface integrity with castor oil (CO) was found to be significantly improvement in surface quality including lower surface roughness (Rα: 0.23 μm and Rz: 1.83 μm) with uniform surface topography, absence of oxidization and carbonization film, and negligible change in microhardness and microstructure. The reason is strong and uniform anti-friction and anti-wear tribo-film was produced by castor oil, which minimizes heat penetration through limited ploughing and rubbing action. The MBN outcome i.e., root mean square (RMS) has followed a linear relation with microhardness and temperature of the ground sample with a correlation coefficient of 0.993 and 0.981. Besides, lower amplitude and wide peak envelope get shifted towards a higher magnetic field in the MQL-CO grinding caused by poor thermal softening effect on the ground sample, which restricts magnetic domain wall movement and rotation. These outcomes could guide tooling industries for efficient sustainable grinding with faster thermal damage assessment, which helps to minimize production cycle time and back to clean environment. © 2023